ANALISIS STRATEGI PEMBELAJARAN GURU DALAM MENINGKATKAN KEMAMPUAN MEMAHAMI ISI BACAAN MATERI BERCERITA DI KELAS III SD NEGERI 02 BEDUAI - Sukristin Sukristin; Amin Mustajab; Andreana Ayuwina (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2023)
Abstract: The background of this research is that there are still many students who are less able to understand the learning material concerned with storytelling material. The purpose of this research is to find out the inquiry learning strategy used to improve the ability to understand the content of reading material in storytelling. The research method is a qualitative descriptive research with research design: interviews, dukumentation observation. The subjects in this study were class III teacher at Elementary Scholl Negeri 02 Beduai. The data analysis technique uses 3 stages, namely, data reduction, data presentation and conclusion drawing as well as testing the validity of the data. Based on the research results using indicators of understanding the contents of the reading or assessment criteria, namely. The ability to grasp the meaning of word and expressions used by the author, the ability to grasp the explicit and implied meanings and the ability to draw conclusions through inquiry learning strategies. At was found that 35% of the 7 students in the very good category increased to 50% of the 10 students in the very good category. So that it can be concluded that the inquiry learning strategy used in improving students understanding skills in Indonesian language subject storytelling was declared successful. Keywords: Strategy, Teacher Learning, ability to Understand Reading Content. Abstrak: Latar belakang penelitian ini adalah masih banyak peserta didik yang kurang mampu memahami materi pembelajaran yang bersangkutan dengan materi bercerita. Tujuan dalam penelitian ini adalah mengetahui strategi pembelajaran inkuiri yang digunakan untuk meningkatkan kemampuan memahami isi bacaan dalam materi bercerita. Metode penelitiaan adalah penelitian deskriptif kualitatif dengan desain penelitian: wawancara, observasi, dokumentasi. Subjek dalam penelitian ini adalah guru kelas III SD Negeri 02 Beduai. Teknik analisis data menggunakan 3 tahap yaitu, reduksi data, penyajian data dan penarikan kesimpulan serta uji keabsahan data. Berdasarkan hasil penelitian menggunakan indikator memahami isi bacaan atau kriteria penilaian yaitu, kemampuan menangkap arti kata dan ungkapan yang digunakan penulis, kemampuan menangkap makna tersurat dan makna tersirat dan kemampuan membuat kesimpulan melalui strategi pembelajaran inkuiri. Diperoleh 35% dari 7 peserta didik kategori sangat baik meningkat menjadi 50% dari 10 peserta didik dengan ketegori sangat baik. Sehingga dapat disimpulkan strategi pembelajaran inkuiri yang digunakan dalam meningkatkan kemampuan pemahaman peserta didik pada mata pelajaran bahasa indonesia materi bercerita dinyatakan berhasil. Kata Kunci: Strategi, Pembelajaran Guru, Kemampuan Memahami Isi Bacaan.